Timing of nitrogen fertilization and shading affect the transition of nitrogen metabolism in senescing leaves of ripening wheat (Triticum aestivum L.) - Hideki Araki; Hirotaka Ueno; Keisuke Mizuta; Tadashi Takahashi; Masaru Shibata; Jun’ichi Mano (Plant Production Science)
The grain yield and protein content of wheat is influenced by the transition of nitrogen metabolism in senescing leaves from pre-anthesis to maturity. To characterize the biochemical processes of the transition, we here analyzed the interactions among greenness, soluble protein, amino acid and protease activity in the flag and second leaves of ripening wheat plants. Nitrogen regimes were adjusted by intensive nitrogen applications in the early (IN (E)) or late stages (IN (L)) along with or without top-dressing at anthesis (±TD). The progress of leaf nitrogen metabolism towards terminal senescence appeared to be split into two phases: the first phase (from pre-anthesis to about 15 days after anthesis (DAA), when leaf greenness did not change appreciably) was characterized by a decrease in soluble protein, and the second phase (after 15 DAA) was characterized by drastic increases in the protease activity followed by a rapid decrease in leaf greenness. The decrease in soluble proteins during the first phase was not accompanied by a rise in protease activity. The rise in protease activity during the second phase was most apparent in the IN (E)-TD plants that were likely under the most severe nitrogen starvation among the treatments. The IN (L) and TD were effective to defer the leaf senescence processes. The shading treatment delayed the rise in protease activity and decrease in leaf greenness. This study suggests that the terminal leaf senescence proceeds in two phases, and the transition between these was accelerated by low nitrogen and slowed by mild shading.